The Scottish credit and qualifications framework : lessons for the EQF - Raffe, David [Verfasser]; Gallacher, Jim [Verfasser]; Toman, Nuala [Verfasser] (My University, 2008)
"The SCQF is one of the longest-established comprehensive quali?cations frameworks and is often perceived as one of the most successful. This article describes the main features of the SCQF and outlines its progress, drawing on recent studies and evaluations by the authors. It draws lessons for the EQF and for further development of national frameworks to respond to it. These lessons concern the speci?c requirements of meta-frameworks and comprehensive frameworks, the need for realistic expectations and time scales, and the value of an incremental and pragmatic strategy for introducing a learning-outcomes approach. The article also identi?es issues relating to the architecture of a levels framework and the limitations, as well as strengths, of a voluntary partnership-based approach." (author's abstract, BIBB-Doku)
Das schottische Rahmensystem für Anrechnungseinheiten und Qualifikationen (SCQF)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2.1 Westeuropa; Europäischer Qualifikationsrahmen; Nationaler Qualifikationsrahmen; Schottland; Wales; England; Irland; Nordirland; Vereinigtes Königreich